Some new Cesàro sequence spaces of order α - Savaşcı, Medine Yeşilkayagil; Başar, Feyzi (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.98 We introduce the spaces _∞(C_α), f(C_α), and f_0(C_α) of Cesàro bounded, Cesàro almost convergent, and Cesàro almost null sequences of order α, respectively. Moreover, we establish some inclusion relations for these spaces and determine the α-, β- and γ-duals of the spaces _∞(C_α) and f(C_α). Finally, we characterize the classes of matrix transformations from the space f(C_α) to any sequence space Y and from any sequence space Y to the space f(C_α).